A Vietnamese-English cross-cultural study on the use of responding to English greetings - Phùng, Thị Đức (ĐHNN, 2017)
This study consists of three main parts. Part I-Introduction-In this first part, all the theoretical background and academic routines are discussed. In part B–Development focuses on the 3 chapters. In chapter I, cross-cultural and responding to a greeting are defined cultural pragmatics and replying a greeting are mentioned. In this chapter, the author distinguishes the differences and the similarities between responding to greeting in English and Vietnamese. In the next chapter, the research methodology is discussed with analysis and findings from the survey questionnaires conducted by the Vietnamese and English. Part III is the conclusion of the study, here, the author summarize all the main ideas, the important findings as well as some suggestion